Causal/Noncausal Verb Pairs in Barpak Ghale - Yoshida, Shigeki (Nepalese Linguistics, 2024)
This study aims to investigate the coding strategies used for causal and non-causal verb pairs in Barpak Ghale, a Tamangic language of Nepal. Methodologically, it examines the strategies employed for 31 verb pairs provided by Haspelmath (1993). There are three major findings. First, Barpak Ghale has five coding strategies including anti-causative, causative, labile, equipollent, and suppletive with a few sub types in each strategy. Second, this study analyzes tone-differentiated verb pairs as exhibiting anti causative derivation based on the direction of neutralization. Third, the comparison of Barpak Ghale with other Tibeto-Burman languages shows that the language has fewer causative verb pairs.